A broad conception of critique. Nancy Fraser and the question of neoliberalism - Giachetti, Fulvia (Scenari, 2023)
The article reconstructs and investigates Nancy Fraser’s analysis of “neoliberal” capitalism, interpreting it as an attempt to rehabilitate Marxist critique in the face of the historical novelty that emerged in the 1980s, which undermined its conditions of possibility. In particular, the essay shows how the tension between neoliberalism and critique is at the core of Fraser’s reflection, leading the philosopher, over the years, to rethink her conception of critique itself. This marks a shift from a democratic theory of “participatory parity” to what can be called a theory of “class justice”, where the class subject, analysed by Fraser, far from being thought of from an economicist perspective, challenges, and brings to light, the co-dependence between economic and extra-economic realities that defines its condition.